Respiratory health status is impaired in UK HIV‐positive adults with virologically suppressed HIV infection. Issue 8 (13th March 2017) - Brown, J; McGowan, JA; Chouial, H; Capocci, S; Smith, C; Ivens, D; Johnson, M; Sathia, L; Shah, R; Lampe, FC; Rodger, A; Lipman, M
Abstract : Objectives: We sought to evaluate whether people living with HIV (PLWH) using effective antiretroviral therapy (ART) have worse respiratory health status than similar HIV‐negative individuals. Methods: We recruited 197 HIV‐positive and 93 HIV‐negative adults from HIV and sexual health clinics. They completed a questionnaire regarding risk factors for respiratory illness. Respiratory health status was assessed using the St George's Respiratory Questionnaire (SGRQ) and the Medical Research Council (MRC) breathlessness scale. Subjects underwent spirometry without bronchodilation. Results: PLWH had worse respiratory health status: the median SGRQ Total score was 12 [interquartile range (IQR) 6–25] in HIV‐positive subjects vs . 6 (IQR 2–14) in HIV‐negative subjects ( P  < 0.001); breathlessness was common in the HIV‐positive group, where 47% compared with 24% had an MRC breathlessness score ≥ 2 ( P  = 0.001). Eighteen (11%) HIV‐positive and seven (9%) HIV‐negative participants had airflow obstruction. In multivariable analyses (adjusted for age, gender, smoking, body mass index and depression), HIV infection remained associated with higher SGRQ and MRC scores, with an adjusted fold‐change in SGRQ Total score of 1.54 [95% confidence interval (CI) 1.14–2.09; P  = 0.005] and adjusted odds ratio of having an MRC score of ≥ 2 of 2.45 (95% CI 1.15–5.20; P  = 0.02). Similar findings were obtained when analyses were repeated including only HIV‐positive participants with a viral load < 40 HIV‐1 RNA copies/mL. Conclusions: Despite effective ART, impaired respiratory health appears more common in HIV‐positive adults, and has a significant impact on health‐related quality of life.